Corrective Feedback and Iranian EFL Learners' Spoken Complexity and Accuracy - Farahman Farrokhi; Mohammad Zohrabi; Mohammad Hassan Chehr Azad (Teaching English Language, 2018)
One of the possible negative consequences of the corrective feedback (CF), as a way of focus on form, can be a trade-off between the learners' spoken complexity and accuracy, due to their attentional limitations. Consequently, the purpose of the current study was to investigate the effects of the different CF types on Iranian EFL learners' spoken complexity and accuracy and the trade-off between them. To this end, four preintermediate intact classes were randomly selected as the delayed explicit metalinguistic CF, intensive recast, extensive recast, and control groups. All groups' participants participated in spoken reproduction tasks for six sessions and their errors were treated differently. Then, the data were transcribed, coded for the complexity and accuracy, and statistically analyzed. The results indicated that different CF types had insignificant effects on the complexity of the spoken production. However, the delayed explicit metalinguistic CF group significantly increased the spoken specific accuracy. Considering the trade-off between the spoken complexity and accuracy, it was revealed that the correlations between them was statistically insignificant and different CF conditions had no significant effect on it. These findings suggest that CF, of the delayed explicit metalinguistic type, can be an effective way for the development of the spoken specific accuracy of the Iranian EFL learners. In addition, its development has no negative effects on their spoken complexity.